2015
DOI: 10.1111/jvp.12244
|View full text |Cite
|
Sign up to set email alerts
|

The acute phase response induced by Escherichia coli lipopolysaccharide modifies the pharmacokinetics and metabolism of florfenicol in rabbits

Abstract: The aim of this study was to determine the effect of Escherichia coli lipopolysaccharide (LPS)-induced acute phase response (APR) on the pharmaco-kinetics and biotransformation of florfenicol (FFC) in rabbits. Six rabbits (3.0 ± 0.08 kg body weight (bw)) were distributed through a crossover design with 4 weeks of washout period. Pairs of rabbits similar in bw and sex were assigned to experimental groups: Group 1 (LPS) was treated with three intravenous doses of 1 μg/kg bw of E. coli LPS at intervals of 6 h, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…The results of an experimental inflammation study involving rabbits demonstrated that while plasma CRP concentrations were lower than 10 µg/ml in control rabbits, CRP concentrations started to increase at 6 h after turpentine injection and peaked at 514 µg/ml at 36 h [14]. In another study involving rabbits, after three intravenous injection of LPS at 6-h intervals, the mean serum CRP concentration was 81.4 ± 3.3 µg/ml at 24 h [30]. In our study, the peak serum CRP concentration was 242.70 ± 70.43 µg/ml at 8 h. In EG, the mean serum CRP concentration initially increased at 8 h. Although serum CRP concentration changes were measured to follow the systemic inflammatory response in the present study, serum LDH concentrations quickly increased before serum CRP concentrations increased.…”
Section: Discussionmentioning
confidence: 99%
“…The results of an experimental inflammation study involving rabbits demonstrated that while plasma CRP concentrations were lower than 10 µg/ml in control rabbits, CRP concentrations started to increase at 6 h after turpentine injection and peaked at 514 µg/ml at 36 h [14]. In another study involving rabbits, after three intravenous injection of LPS at 6-h intervals, the mean serum CRP concentration was 81.4 ± 3.3 µg/ml at 24 h [30]. In our study, the peak serum CRP concentration was 242.70 ± 70.43 µg/ml at 8 h. In EG, the mean serum CRP concentration initially increased at 8 h. Although serum CRP concentration changes were measured to follow the systemic inflammatory response in the present study, serum LDH concentrations quickly increased before serum CRP concentrations increased.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados demuestran que existen diferencias significativas entre estas especies en términos de la distribución del fármaco y su metabolito en plasma y tejidos, lo que indica diferencias de especie en los procesos farmacocinéticos. Se ha estudiado previamente la farmacocinética de FFC y FFC-a posterior a la administración IV de FFC en ovinos (10) y conejos (3). Posterior a la inyección IV de una dosis de FFC de 20 mg/kg, las principales diferencias en la farmacocinética observadas entre estas dos especies se relacionaron con la vida media de eliminación y AUC 0-t -las que fueron más elevadas en ovinos que en conejos.…”
Section: Discussionunclassified
“…La validación de la metodología analítica en tejidos de ovinos fue previamente descrita en nuestro laboratorio por Pérez et al (22), y parámetros como linealidad (r2), recuperación (%), precisión (CV%), límite de detección (LOD) y límite de cuantificación (LOQ) fueron determinados. La validación del método analítico en plasma de conejos fue previamente descrito por Pérez et al (3). La metodología analítica en tejidos de conejos fue validada y entregó valores de recuperación promedio total de FFC y FFC-a de 82.22 ± 5.7% y 81.72 ± 3.8%, respectivamente.…”
Section: Parámetros De Validación De Ffc Y Ffc-aunclassified
See 1 more Smart Citation
“…There is evidence indicating that the pharmacokinetics of drugs vary during the occurrence of a pathological state or an infection that involves an inflammatory component, therefore, the ability to handle these drugs is diminished (RENTON, 2005), these effects result from the altered expression of certain enzymes of the Cytochrome P450 family (CYP 450) and of drug transport proteins, which are regulated downward (down regulation) during the generation of host defense mechanisms (MORGAN et al, 2008) . This has been demonstrated by different studies where significant modifications in the pharmacokinetics of drugs have been observed between animals treated LPS and control animals (GORALSKI et al, 2003;ELMAS et al, 2006;PÉREZ et al, 2015;PÉREZ et al, 2016).…”
Section: Resultsmentioning
confidence: 84%